The impact of COVID-19 on mortality after hip fracture: a population cohort study from England. (11th August 2022) - Holleyman, Richard J.; Khan, Sameer K.; Charlett, Andre; Inman, Dominic S.; Johansen, Antony; Brown, Colin; Barnard, Sharmani; Fox, Sebastian; Baker, Paul N.; Deehan, David; Burton, Paul; Gregson, Celia L.
Abstract : Aims: Hip fracture commonly affects the frailest patients, of whom many are care-dependent, with a disproportionate risk of contracting COVID-19. We examined the impact of COVID-19 infection on hip fracture mortality in England. Methods: We conducted a cohort study of patients with hip fracture recorded in the National Hip Fracture Database between 1 February 2019 and 31 October 2020 in England. Data were linked to Hospital Episode Statistics to quantify patient characteristics and comorbidities, Office for National Statistics mortality data, and Public Health England's SARS-CoV-2 testing results. Multivariable Cox regression examined determinants of 90-day mortality. Excess mortality attributable to COVID-19 was quantified using Quasi-Poisson models. Results: Analysis of 102, 900 hip fractures (42, 630 occurring during the pandemic) revealed that among those with COVID-19 infection at presentation (n = 1, 120) there was a doubling of 90-day mortality; hazard ratio (HR) 2.09 (95% confidence interval (CI) 1.89 to 2.31), while the HR for infections arising between eight and 30 days after presentation (n = 1, 644) the figure was greater at 2.51 (95% CI 2.31 to 2.73). Malnutrition (1.45 (95% CI 1.19 to 1.77)) and nonoperative treatment (2.94 (95% CI 2.18 to 3.95)) were the only modifiable risk factors for death in COVID-19-positive patients. Patients who had tested positive for COVID-19 more than two weeks prior to hip fracture initially had better survival compared to those who contracted COVID-19 around the time of their hip fracture; however, survival rapidly declined and by 365 days the combination of hip fracture and COVID-19 infection was associated with a 50% mortality rate. Between 1 January and 30 June 2020, 1, 273 (99.7% CI 1, 077 to 1, 465) excess deaths occurred within 90 days of hip fracture, representing an excess mortality of 23% (99.7% CI 20% to 26%), with most deaths occurring within 30 days. Conclusion: COVID-19 infection more than doubles the rate of early hip fracture mortality. Those contracting infection between 8 and 30 days after initial presentation are at even higher mortality risk, signalling the potential for targeted interventions during this period to improve survival. Cite this article: Bone Joint J  2022;104-B(10):1156–1167.